Validasi Metode Kromatografi Cair Kinerja Tinggi Untuk Analisis Rhodamin B Dalam Saos Tomat - Yantih, Novi; Aziz, Zuhelmi; Aprillia, Heidy (Indonesian Research Gateway)
Rhodamine B is a synthetic red dye which is commonly used as textile dyes and banned its use in food and beverages. The red dye is harmful to health and it can cause poisoning symptoms if it is swallowed, and it can damage the liver when it is taken long term. Although it has been banned because of its toxicity, but there is abuse of rhodamine B as a food coloring, such as in tomato sauce product. The purpose of this study is to validate the high performance liquid chromatography (HPLC) for analysis of rhodamine B in a tomato sauce. The analytical method used is HPLC with reverse phase system. The analytical method has met the requirements of method validation according to the International Conference of Harmonization with the detection and quantitation limits, 1 ppm and 3 ppm respectively. Based on the results of the qualitative analysis of rhodamine B in tomato sauce samples, one of the three samples of tomato sauce that is not listed in NA-DFC (The National Agency of Drug and Food Control) showed positive result, it was shown with the same retention time between samples and standards (5.5 minutes). Average level of rhodamine B in the sample was 25 μg/g of tomato sauce.